Primary loop analysis for a PWR contains Passive Core Cooling System; LOCA and clad rising temperature. (May 2016) - Porhemmat, M.H.; Faghihi, F.; Rabiee, A.
Highlights: A reduced order primary model (RPM) is examined for the primary loop of a modern PWR which includes passive safety guards. Fundamental neutronics and thermal–hydraulics equations for the primary loop of a modern PWR are investigated based on RPM. Two break size of LOCA is modelled using RPM, and results are benchmarked by RELAP5/mode 3 code. Loss of primary pumps and diesel generators due to Tsunami scenario are supposed. Based on RPM and described design basis accident scenario, clad rising temperature are investigated. Abstract: This article contains a Reduced Primary Model (RPM) for estimating the primary dynamical responses, based on fundamental governing equations, clad temperature rising estimation after occurring the LOCA for a modern PWR are carried out. Explicitly, a model for primary loop of a modern PWR (called RPM) is proposed herein for LOCA modelling. We have supposed an accident scenario, which only Passive Core Cooling Systems (PCCS) are in order, and based on the RPM, primary dynamical responses according to fundamental governing equations are determined and then our results are benchmarked by the RELAP5.2 code. Clad rising temperature is calculated during five minutes loss of time to remove decay heat using the lumped parameter technique. Based on our calculations, clad temperature rising is lower than its safety margin and the suggested modern PWR is safe under grisly accident which is described herein.